Development and performance evaluation of the electric-hydraulic concave clearance control system based on maize feed rate monitoring - Fan, Chenlong; Zhang, Dongxing; Yang, Li; Cui, Tao; He, Xiantao; Zhao, Huihui (International Journal of Agricultural and Biological Engineering, 2022)
Complex field environments, diverse crop conditions, and varying feed rate fluctuations commonly result in a decline in the threshing performance and the clogging of the threshing cylinder for maize harvesters. In order to overcome these problems, an electric-hydraulic concave clearance automatic control system for the threshing unit was developed based on the maize feed rate monitoring, which can automatically realize the best match between the concave clearance and diverse feed rates during harvesting. The threshing performance of the electric-hydraulic control system was evaluated for varying and uneven maize feed rate fluctuations, such as the feed rate increased (6-8-10 kg/s), the feed rate decreased after an increase (6-10-8 kg/s, 8-10-6 kg/s), the feed rate increased after a decrease (8-6-10 kg/s, 10-6-8 kg/s), and the feed rate decreased (10-8-6 kg/s). In particular, the threshing rotor shaft peak torque, the range of threshing rotor shaft torque, the rate of broken grains (BGR), and the rate of unthreshed grains (UGR) with and without the electric-hydraulic control system were tested. Treatments with the electric-hydraulic control system were adjustable concave clearance with the value of 45 mm, 50 mm, and 55 mm. Treatments without the electric-hydraulic control system were constant concave clearance (50 mm). Results demonstrate that the threshing unit with the electric-hydraulic control system outperformed the one without the electric-hydraulic control system, with threshing rotor peak torque, the range of threshing rotor axis torque, the BGR, and the UGR decreasing by 18.38%, 38.27%, 2.08%, and 0.10%, respectively. Moreover, the rate of broken grains was lower than 5.00%, better than the national standard. Thus, the feed rate fluctuations and timely adjustment of the concave clearance were able to avoid blocking the rotor and improve the threshing performance compared to the constant concave clearance. Keywords: maize harvester, threshing cylinder, feed rate, concave clearance, electro-hydraulic control system DOI: 10.25165/j.ijabe.20221502.6369 Citation: Fan C L, Zhang D X, Yang L, Cui T, He X T, Zhao H H. Development and performance evaluation of the electric-hydraulic concave clearance control system based on maize feed rate monitoring. Int J Agric & Biol Eng, 2022; 15(2): 156–164.